1987
DOI: 10.1093/clinchem/33.8.1391
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of sensitive assays of thyrotropin (TSH) used to screen for thyroid disease in hospitalized patients.

Abstract: Thyrotropin (TSH) concentrations were measured in 1580 hospitalized patients and 109 normal persons. Using the mean +/- 3 SD limits of the log values for the controls (0.35-6.7 milli-int. units/L), the proportion of abnormal TSH results in the hospitalized patients was 17.2%. TSH was undetectable (less than 0.1 milli-int. unit/L) in 3.1% of patients, suggesting hyperthyroidism, and high (greater than 20 milli-int. units/L) in 1.6%, suggesting hypothyroidism. On follow-up of 329 patients, 62% with abnormal TSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(53 citation statements)
references
References 0 publications
1
49
1
2
Order By: Relevance
“…2). Other authors also reported a lower mean sTSH concentration in a group of NTT patients compared to normal (Boles et ul., 1987) and a higher incidence of suppressed sTSH values in NTI patients (Wehmann et al, 1985;Dubuis & Burger, 1986;Spencer et al, 1987;Ehrmann et al, 1989), but the total number of patients in thesc studies is much smaller. The patient selection in thcse latter studies was different from the previously mentioned series, for instance, patients receiving drugs known to suppress pituitary TSH secretion, such as corticosteroids (Faglia at al., 1973;Re et al, 1976) or dopamine (Besses et ul., 1975;Kaptein et al, 1980b), were not excluded from the study, nor were those with thyroid disease (Spencer et a/., 1987).…”
Section: Serum Tsh Concentrationmentioning
confidence: 89%
See 3 more Smart Citations
“…2). Other authors also reported a lower mean sTSH concentration in a group of NTT patients compared to normal (Boles et ul., 1987) and a higher incidence of suppressed sTSH values in NTI patients (Wehmann et al, 1985;Dubuis & Burger, 1986;Spencer et al, 1987;Ehrmann et al, 1989), but the total number of patients in thesc studies is much smaller. The patient selection in thcse latter studies was different from the previously mentioned series, for instance, patients receiving drugs known to suppress pituitary TSH secretion, such as corticosteroids (Faglia at al., 1973;Re et al, 1976) or dopamine (Besses et ul., 1975;Kaptein et al, 1980b), were not excluded from the study, nor were those with thyroid disease (Spencer et a/., 1987).…”
Section: Serum Tsh Concentrationmentioning
confidence: 89%
“…Furthermore, it seems that the rise in serum rT3 precedes the fall in T3 in mild rorms of illness. Serum TSH levels as measured with a second generation assay are usually normal in all groups, but may be reduced or elevated (Spencer et al, 1987;Krenning el d., 1987), while the TSH response to T R H may be blunted (Wartofsky & Burman, 1982). Spencer et 01.…”
Section: Effects On Thyroid Hormone Parameters In Serummentioning
confidence: 99%
See 2 more Smart Citations
“…Although the thyrotrophin-releasing hormone (TRH) stimulation test (Dahlberg et af., 1985;Schleusener et al, 1989) and the T3 suppression test (Alexander et al, 1970;Yamada et al, 1984) have been used widely used for the assessment of the pituitary-thyroid axis, these tests are not suitable for monitoring antithyroid drug treatment in daily practice. Since sensitive TSH measurements are able to distinguish suppressed serum TSH values from euthyroid levels (Klee & Hay, 1987;Spencer et al, 1987), the basal TSH measurement determined by the sensitive immunometric assay can replace the TRH stimulation or T3 suppression test and is more practically useful (Toft, 1988;Nicoloff & Spencer, 1990). Direct measurement of thyroid stimulating antibodies (TSAb) is very helpful for predicting the clinical outcome of Graves' disease (Zakarija e t al., 1980;Edan et al, 1989, Schleusener et a\., 1989.…”
Section: Discuseionmentioning
confidence: 99%